Wild Predators, Livestock, and Free Ranging Dogs: Patterns of Livestock Mortality and Attitudes of People Toward Predators in an Urbanizing Trans-Himalayan Landscape - Pahuja, Meenal; Sharma, Rishi Kumar (Frontiers in Conservation Science, 2021)
Livestock depredation by large carnivores is a significant source of conflicts over predators and an important conservation and economic concern. Preventing livestock loss to wild predators is a substantial focus of human-carnivore conflict mitigation programs. A key assumption of the preventive strategy is reduction in the livestock losses leading to a positive shift in the attitudes towards predators. Therefore, it is important to quantify the true extent of livestock mortality caused by wild predators and its influence on attitudes of the affected communities. We examined seasonal and spatial patterns of livestock mortality and factors influencing people’s attitudes towards wild predators i.e., snow leopards (Panthera uncia) and wolves (Canis lupus chanco) and free-ranging dogs (Canis lupus familiaris) in a Trans-Himalayan urbanizing landscape in India. We used systematic sampling to select the survey households and implemented semi-structured questionnaires to respondents. The sampled villages (n =16) represent a mosaic of urban and agricultural ecosystems within a radius of 40 kilometres of Leh town. In 2016-17, 93% of the sampled households lost livestock to predators, accounting for 0.93 animals per household per year. However, of the total events of livestock mortality, 33% were because of weather/natural events, 24% by snow leopards, 20 % because of disease, 15% because of free-ranging dogs and 9% because of wolves. The annual economic loss per household because of livestock mortality was USD 371, a substantial loss given the average per capita income of USD 270 in the region. Of the total loss, weather/natural events caused highest loss of USD 131 (35%), followed by snow leopards USD 91 (25%), disease USD 87 (24%), free ranging dogs USD 48 (13%) and wolves USD 14 (4%). Despite losing a considerable proportion of livestock (33 %) to wild predators, respondents showed a positive attitude towards them but exhibited neutral attitudes towards free-ranging dogs. Gender emerged as the most important determinant of attitudes towards wild predators, with men showing higher positive attitude score towards wild predators than women. Our findings highlight the context specific variation in human-wildlife interactions and emphasize that generalizations must be avoided in the absence of site specific evidence.